Our knowledge of God from the analogy of being in Thomas Aquinas and Francisco Suárez - Yangali Núñez, Oscar Edmundo (2020)
In this paper I propose to develop how Francisco Suárez’s conception of the analogy of being mutates from a reformulation of the thought of Thomas Aquinas. In accordance with this hypothesis, the suarecian effort will consist of giving us a better expression of the knowledge that we can attain of God by this reformulation of the analogy. First, I develop what is the conception of the Thomistic analogy in relation to our knowledge of God. Second, I show what are the criticisms of Scotus to the said analogy. Third, what semantic changes occur in the concepts used by Suárez and what is his conception of the analogy. Finally, I present the conclusions that sustain that this suarecian interpretation is nothing but a renewed proposal about our knowledge of God and how to participate in Him.